(3JdNjU GdCOdI dbhGYO GdJhMjOs - (3CHh ESMGb EHQGgje Hf ESMGb GdUaGQ GdHNGQjs ((3eMeO Hf CMeO GdMfai s)
(3ChdgG (B:s
(3GdMeO ddg ceG gh Cgdg CeG HYO aEf CMb eG UQaJ Edjg GdYfGjI hHdZJ ai eYQaJg GdZGjI Yde GdOjf GdPi EQJVGg QH GdYGdejf hgh Ojf GdESdGe s
(3BNQgG (B:s
(3bGd GdTjN GdEeGe GdRGgO GdCLd eUfa GdcJGH hGYde HCfG bO CdafG cJGH JdNjU GdCOdI Ydi bOQ eG YbdfGgG dCf GdYde dGjOQc efJbGg UOb Gddg Ld LdGdg (B: ( (3heG ChJjJe ef GdYde EdG bdjdkG (B) (3Je GdcJGH s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B472s
Keywords: (3GdJhMjO hGdedd hGdfMds